From Coronal Holes to Pulsars and Back Again: Learning the Importance of Data - Wang, Y.-M. (Frontiers in Astronomy and Space Sciences, 2022)
Although wanting to become an astronomer from an early age, I ended up in solar physics purely by chance, after first working in high-energy astrophysics. I've never regretted switching from the pulsar to the solar magnetosphere, because solar physics has a great advantage over other areas of astrophysics---in the enormous amount of high-quality data available, much of it underutilized. I've often wondered why theoreticians and modelers don't spent more time looking at these data (perhaps they feel that it's cheating, like taking a peek at the answers to a difficult homework assignment?). Conversely, I wonder why observers and data analysts aren't more skeptical of the theoretical models---especially the fashionable ones.